Negotiating Tradition and Modernity in the Management of Student Care at Islamic Boarding Schools - Muhlasin; Silawati; Muhammad Syaifuddin; Engkizar; Nurjanis; Rifdah Sabrina; Azhar Jaafar (Badan Litbang dan Diklat Kementerian Agama RI, 2026)
This study aims to analyze the management model of Islamic boarding school care in Pekanbaru City. This study employs a qualitative case study methodology. Data collection techniques used interviews and documentation. The results of this study indicate that the management model of Islamic Boarding School care in Pekanbaru consists of modern, semi-traditional, and semi-modern models. These findings have implications for strengthening the concept of care based on Islamic values, the direction of the development of students, effective methods of care, strengthening Islamic boarding school values, the strategic role of musyrif/musyrifah, an integrated development model, a monitoring and evaluation system, flexibility of the care model, strengthening the identity of the Islamic boarding school, and the contribution of Islamic boarding schools in forming a generation of students who are religious, independent, moral, and globally competitive.